Lemma 63.15.1. Let $e\in G$ denote the neutral element. The map

factors through $\Lambda [G]^\natural $. We denote $\varepsilon : \Lambda [G]^\natural \to \Lambda ^\natural $ the induced map.

Notation: We fix the notation for this section. We denote by $A$ a commutative ring, $\Lambda $ a (possibly noncommutative) ring with a ring map $A\to \Lambda $ which image lies in the center of $\Lambda $. We let $G$ be a finite group, $\Gamma $ a *monoid extension of $G$ by $\mathbf{N}$*, meaning that there is an exact sequence

\[ 1\to G\to \tilde\Gamma \to \mathbf{Z}\to 1 \]

and $\Gamma $ consists of those elements of $\tilde\Gamma $ which image is nonnegative. Finally, we let $P$ be an $A[\Gamma ]$-module which is finite and projective as an $A[G]$-module, and $M$ a $\Lambda [\Gamma ]$-module which is finite and projective as a $\Lambda $-module.

Our goal is to compute the trace of $1 \in \mathbf{N}$ acting over $\Lambda $ on the coinvariants of $G$ on $P \otimes _ A M$, that is, the number

\[ \text{Tr}_{\Lambda }\left(1; \left(P \otimes _ A M\right)_ G\right) \in \Lambda ^\natural . \]

The element $1\in \mathbf{N}$ will correspond to the Frobenius.

Lemma 63.15.1. Let $e\in G$ denote the neutral element. The map

\[ \begin{matrix} \Lambda [G]
& \longrightarrow
& \Lambda ^{\natural }
\\ \sum \lambda _ g\cdot g
& \longmapsto
& \lambda _ e
\end{matrix} \]

factors through $\Lambda [G]^\natural $. We denote $\varepsilon : \Lambda [G]^\natural \to \Lambda ^\natural $ the induced map.

**Proof.**
We have to show the map annihilates commutators. One has

\[ \left(\sum \lambda _ g g\right)\left(\sum \mu _ g g\right)-\left(\sum \mu _ g g\right)\left(\sum \lambda _ g g\right) = \sum _ g\left(\sum _{g_1g_2=g} \lambda _{g_1}\mu _{g_2}-\mu _{g_1}\lambda _{g_2}\right)g \]

The coefficient of $e$ is

\[ \sum _ g\left(\lambda _ g\mu _{g^{-1}}-\mu _ g\lambda _{g^{-1}}\right) = \sum _ g\left(\lambda _ g\mu _{g^{-1}}-\mu _{g^{-1}}\lambda _ g\right) \]

which is a sum of commutators, hence it zero in $\Lambda ^\natural $. $\square$

Definition 63.15.2. Let $f : P\to P$ be an endomorphism of a finite projective $\Lambda [G]$-module $P$. We define

\[ \text{Tr}_{\Lambda }^ G(f; P) := \varepsilon \left(\text{Tr}_{\Lambda [G]}(f; P)\right) \]

to be the *$G$-trace of $f$ on $P$*.

Lemma 63.15.3. Let $f : P\to P$ be an endomorphism of the finite projective $\Lambda [G]$-module $P$. Then

\[ \text{Tr}_{\Lambda }(f; P) = \# G \cdot \text{Tr}_\Lambda ^ G(f; P). \]

**Proof.**
By additivity, reduce to the case $P = \Lambda [G]$. In that case, $f$ is given by right multiplication by some element $\sum \lambda _ g\cdot g$ of $\Lambda [G]$. In the basis $(g)_{g \in G}$, the matrix of $f$ has coefficient $\lambda _{g_2^{-1}g_1}$ in the $(g_1, g_2)$ position. In particular, all diagonal coefficients are $\lambda _ e$, and there are $\# G$ such coefficients.
$\square$

Lemma 63.15.4. The map $A\to \Lambda $ defines an $A$-module structure on $\Lambda ^\natural $.

**Proof.**
This is clear.
$\square$

Lemma 63.15.5. Let $P$ be a finite projective $A[G]$-module and $M$ a $\Lambda [G]$-module, finite projective as a $\Lambda $-module. Then $P \otimes _ A M$ is a finite projective $\Lambda [G]$-module, for the structure induced by the diagonal action of $G$.

Note that $P \otimes _ A M$ is naturally a $\Lambda $-module since $M$ is. Explicitly, together with the diagonal action this reads

\[ \left(\sum \lambda _ g g\right)\left(p \otimes m\right) = \sum g p \otimes \lambda _ g g m. \]

**Proof.**
For any $\Lambda [G]$-module $N$ one has

\[ \mathop{\mathrm{Hom}}\nolimits _{\Lambda [G]}\left(P \otimes _ A M, N\right)= \mathop{\mathrm{Hom}}\nolimits _{A[G]}\left(P, \mathop{\mathrm{Hom}}\nolimits _{\Lambda }(M, N)\right) \]

where the $G$-action on $\mathop{\mathrm{Hom}}\nolimits _{\Lambda }(M, N)$ is given by $(g\cdot \varphi )(m) = g \varphi (g^{-1} m) $. Now it suffices to observe that the right-hand side is a composition of exact functors, because of the projectivity of $P$ and $M$. $\square$

Lemma 63.15.6. With assumptions as in Lemma 63.15.5, let $u\in \text{End}_{A[G]}(P)$ and $v\in \text{End}_{\Lambda [G]}(M)$. Then

\[ \text{Tr}_\Lambda ^ G \left(u \otimes v; P \otimes _ A M\right) = \text{Tr}_ A^ G(u; P)\cdot \text{Tr}_\Lambda (v;M). \]

**Sketch of proof.**
Reduce to the case $P=A[G]$. In that case, $u$ is right multiplication by some element $a = \sum a_ gg$ of $A[G]$, which we write $u = R_ a$. There is an isomorphism of $\Lambda [G]$-modules

\[ \begin{matrix} \varphi :
& A[G]\otimes _ A M
& \cong
& \left(A[G]\otimes _ A M\right)'
\\ & g \otimes m
& \longmapsto
& g \otimes g^{-1}m
\end{matrix} \]

where $\left(A[G]\otimes _ A M\right)'$ has the module structure given by the left $G$-action, together with the $\Lambda $-linearity on $M$. This transport of structure changes $u \otimes v$ into $\sum _ ga_ gR_ g \otimes g^{-1}v$. In other words,

\[ \varphi \circ (u \otimes v) \circ \varphi ^{-1} = \sum _ ga_ gR_ g \otimes g^{-1}v. \]

Working out explicitly both sides of the equation, we have to show

\[ \text{Tr}_\Lambda ^ G\left(\sum _ g a_ gR_ g \otimes g^{-1}v\right) = a_ e\cdot \text{Tr}_\Lambda (v; M). \]

This is done by showing that

\[ \text{Tr}_\Lambda ^ G\left(a_ gR_ g \otimes g^{-1}v\right) = \left\{ \begin{matrix} 0
& \text{ if } g\neq e
\\ a_ e\text{Tr}_\Lambda \left(v; M\right)
& \text{ if }g = e
\end{matrix} \right. \]

by reducing to $M=\Lambda $. $\square$

Notation: Consider the monoid extension $1 \to G\to \Gamma \to \mathbf{N} \to 1$ and let $\gamma \in \Gamma $. Then we write $Z_\gamma = \{ g\in G | g\gamma = \gamma g\} $.

Lemma 63.15.7. Let $P$ be a $\Lambda [\Gamma ]$-module, finite and projective as a $\Lambda [G]$-module, and $\gamma \in \Gamma $. Then

\[ \text{Tr}_{\Lambda }(\gamma , P) = \# Z_\gamma \cdot \text{Tr}_\Lambda ^{Z_\gamma }\left(\gamma , P\right). \]

**Proof.**
This follows readily from Lemma 63.15.3.
$\square$

Lemma 63.15.8. Let $P$ be an $A[\Gamma ]$-module, finite projective as $A[G]$-module. Let $M$ be a $\Lambda [\Gamma ]$-module, finite projective as a $\Lambda $-module. Then

\[ \text{Tr}_{\Lambda }^{Z_\gamma }(\gamma , P \otimes _ A M) = \text{Tr}_ A^{Z_\gamma }(\gamma , P)\cdot \text{Tr}_\Lambda (\gamma , M). \]

**Proof.**
This follows directly from Lemma 63.15.6.
$\square$

Lemma 63.15.9. Let $P$ be a $\Lambda [\Gamma ]$-module, finite projective as $\Lambda [G]$-module. Then the coinvariants $P_ G = \Lambda \otimes _{\Lambda [G]} P$ form a finite projective $\Lambda $-module, endowed with an action of $\Gamma /G = \mathbf{N}$. Moreover, we have

\[ \text{Tr}_\Lambda (1; P_ G) = \sum \nolimits '_{\gamma \mapsto 1} \text{Tr}_\Lambda ^{Z_\gamma }(\gamma , P) \]

where $\sum _{\gamma \mapsto 1}'$ means taking the sum over the $G$-conjugacy classes in $\Gamma $.

**Sketch of proof.**
We first prove this after multiplying by $\# G$.

\[ \# G\cdot \text{Tr}_\Lambda (1; P_ G) = \text{Tr}_\Lambda (\sum \nolimits _{\gamma \mapsto 1} \gamma , P_ G) = \text{Tr}_\Lambda (\sum \nolimits _{\gamma \mapsto 1} \gamma , P) \]

where the second equality follows by considering the commutative triangle

\[ \xymatrix{ P^ G \ar[rd]_ a & & P_ G \ar[ll]^ c \\ & P \ar[ur]_ b } \]

where $a$ is the canonical inclusion, $b$ the canonical surjection and $c = \sum _{\gamma \mapsto 1} \gamma $. Then we have

\[ (\sum \nolimits _{\gamma \mapsto 1} \gamma ) |_ P = a \circ c \circ b \quad \text{and}\quad (\sum \nolimits _{\gamma \mapsto 1} \gamma ) |_{P_ G} = b \circ a \circ c \]

hence they have the same trace. We then have

\[ \# G\cdot \text{Tr}_\Lambda (1; P_ G) = {\sum _{\gamma \mapsto 1}}' \frac{\# G}{\# Z_\gamma }\text{Tr}_\Lambda (\gamma , P) = \# G{\sum _{\gamma \mapsto 1}}' \text{Tr}_\Lambda ^{Z_\gamma }(\gamma , P). \]

To finish the proof, reduce to case $\Lambda $ torsion-free by some universality argument. See [SGA4.5] for details. $\square$

Remark 63.15.10. Let us try to illustrate the content of the formula of Lemma 63.15.8. Suppose that $\Lambda $, viewed as a trivial $\Gamma $-module, admits a finite resolution $ 0\to P_ r\to \ldots \to P_1 \to P_0\to \Lambda \to 0 $ by some $\Lambda [\Gamma ]$-modules $P_ i$ which are finite and projective as $\Lambda [G]$-modules. In that case

\[ H_*\left(\left(P_\bullet \right)_ G\right) = \text{Tor}_*^{\Lambda [G]}\left(\Lambda , \Lambda \right) = H_*(G, \Lambda ) \]

and

\[ \text{Tr}_\Lambda ^{Z_\gamma }\left(\gamma , P_\bullet \right) =\frac{1}{\# Z_\gamma }\text{Tr}_\Lambda (\gamma , P_\bullet )=\frac{1}{\# Z_\gamma }\text{Tr}(\gamma , \Lambda ) = \frac{1}{\# Z_\gamma }. \]

Therefore, Lemma 63.15.8 says

\[ \text{Tr}_\Lambda (1 , P_ G) = \text{Tr}\left(1 |_{H_*(G, \Lambda )}\right) = {\sum _{\gamma \mapsto 1}}'\frac{1}{\# Z_\gamma }. \]

This can be interpreted as a point count on the stack $BG$. If $\Lambda = \mathbf{F}_\ell $ with $\ell $ prime to $\# G$, then $H_*(G, \Lambda )$ is $\mathbf{F}_\ell $ in degree 0 (and $0$ in other degrees) and the formula reads

\[ 1 = \sum \nolimits _{ \frac{\sigma \text{-conjugacy}}{\text{classes}\langle \gamma \rangle } } \frac{1}{\# Z_\gamma } \mod \ell . \]

This is in some sense a “trivial” trace formula for $G$. Later we will see that (63.14.3.1) can in some cases be viewed as a highly nontrivial trace formula for a certain type of group, see Section 63.30.

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)